A Framework For Cohesive Healthcare Coalition Formation. - Cheah, Yu N; Chong, Yong Han; Neoh, Siew Lan (2006)
The mobilisation of cohesive and effective groups of healthcare human resource is important in ensuring the success of healthcare organisatlons.